Pemanfataan Website Sebagai Media Promosi Wisata Religi Nagari Sirukam - Dira Rahmadani; Nazwa Aurellia Putri; Zola Permata Sari; Sularno .; Novadilastri . (CV. ITTC INDONESIA, 2026)
The rapid development of information technology has encouraged the use of digital media as an effective promotional tool in the tourism sector, including religious tourism destinations. Religious Tourism in Nagari Sirukam, Solok Regency, is a destination with significant historical and cultural value, particularly through the presence of the Tomb of Syech Junjungan Sati and the Modern Surau. However, the limited use of digital promotional media has resulted in the destination receiving relatively low public recognition. This study aims to design a website as a digital promotional medium to introduce the tourism potential of Religious Tourism in Nagari Sirukam to both local communities and prospective visitors. The study employed a descriptive qualitative method using a Project-Based Learning (PBL) approach. Data were collected through direct observation, interviews with tourism managers and community leaders, and documentation from various official sources. The website was developed using the Site123 platform and provides information on the history of Syech Junjungan Sati, tourist attractions, photo galleries, visitor information, and management contact details. The results indicate that the designed website serves as an accessible and informative digital promotional medium that supports the enhancement of the destination’s image and attractiveness. The website is expected to expand promotional outreach, increase tourist visits, and contribute to the preservation of the historical and cultural values of Religious Tourism in Nagari Sirukam.